The Meaning of Gratitude in Civil Servants - Tri Anggono; Demas Tanjung Silain (Universitas Pendidikan Ganesha, 2023)
Gratitude refers to subjective emotions in the form of awe, appreciation, and recognition for everything that has been obtained. Gratitude can also be found in one's job satisfaction and job satisfaction is also an indicator of work attitude, which refers to the overall views and feelings of employees about their work environment and working conditions. The purpose of this research is to understand the meaning of gratitude in civil servants and how this attitude can affect the job satisfaction of civil servants. Based on the research it was concluded that gratitude greatly influences civil servants in their work as well as influences the level of job satisfaction. Gratitude is not only a feeling, but also an attitude, moral nature, habit, nature, and personality, this can affect a person's response to a situation.